2020
DOI: 10.4103/abr.abr_62_20
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cognitive and motor changes revealed by the elevated plus maze in an experimental rat model of radiation-induced brain injury

Abstract: Background: Experimental models are needed to better understand the pathophysiology of neurodegenerative diseases to develop novel therapeutics. The neuropathology and clinical signs of acute radiation syndrome resemble those of neurodegenerative conditions. We characterized elevated plus maze (EPM) indicators of cognitive and motor impairment in rats exposed to brain-damaging doses of gamma radiation to develop a model for neurological component of the acute radiation syndrome. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These can serve as measures for monitoring treatment responses, assessing disease progression, and identifying suitable participant candidates for clinical trials in the LMIC regions. Moreover, the potential of African medicinal plants as novel therapeutic approaches to dementia care in these countries can be better studied within the framework of improved traditional medicines for dementia and related disorders [ 97 , 98 ]. The incorporation of blood biomarkers into clinical trial protocols allows for a more diverse population and comprehensive evaluation of therapeutic interventions, facilitating the monitoring and development of effective treatments.…”
Section: Benefits and Challenging Perspectives Of Using These Circula...mentioning
confidence: 99%
See 1 more Smart Citation
“…These can serve as measures for monitoring treatment responses, assessing disease progression, and identifying suitable participant candidates for clinical trials in the LMIC regions. Moreover, the potential of African medicinal plants as novel therapeutic approaches to dementia care in these countries can be better studied within the framework of improved traditional medicines for dementia and related disorders [ 97 , 98 ]. The incorporation of blood biomarkers into clinical trial protocols allows for a more diverse population and comprehensive evaluation of therapeutic interventions, facilitating the monitoring and development of effective treatments.…”
Section: Benefits and Challenging Perspectives Of Using These Circula...mentioning
confidence: 99%
“…This approach is vital to advocate for action, policy development, and support in the region regarding the importance and urgency of the diagnosis and management of AD and related dementias, as was recently declared in Nairobi during the LMIC conference on dementia [36]. Examples of networks and partnerships established by the Africa Dementia Consortium, Africa Biofluid Brain Biobank (A4B), and the Brain Research Africa Initiative (BRAIN) can be very useful in this regard [99].…”
Section: Stakeholdersmentioning
confidence: 99%
“…These effects were mediated partly by protecting cerebellar neurons from apoptosis and by decreasing neuroinflammation [ 24 , 25 ]. Moreover, we recently reported the ability of G. kola to improve cognitive and motor functions in a rat model of acute radiation syndrome [ 26 27 ]. Interestingly, at the same time, other recent studies also reported G. kola neuroprotective activities in various models of neurodegenerative diseases and conditions [ 28 31 ], calling for further studies to develop neuroprotective drugs from G. kola seeds.…”
Section: Introductionmentioning
confidence: 99%